A low‐protein diet induces body weight loss and browning of subcutaneous white adipose tissue through enhanced expression of hepatic fibroblast growth factor 21 (FGF21). Issue 8 (2nd March 2017) - Pérez‐Martí, Albert; Garcia‐Guasch, Maite; Tresserra‐Rimbau, Anna; Carrilho‐Do‐Rosário, Alexandra; Estruch, Ramon; Salas‐Salvadó, Jordi; Martínez‐González, Miguel Ángel; Lamuela‐Raventós, Rosa; Marrero, Pedro F.; Haro, Diego; Relat, Joana
Abstract : In mice, a low protein diet induces a huge increase in liver FGF21 expression and serum levels, which correlates with enhanced ATF4 protein levels. Also, this diet caused an FGF21‐dependent browning of subcutaneous white adipose tissue. The observation of an inverse relationship between serum levels of FGF21 and dietary protein content also in humans suggests that the induction of hepatic FGF21 expression by a low protein diet could offer an effective treatment for obesity and type 2 diabetes. Abstract : Scope: Fibroblast growth factor 21 (FGF21) is considered a promising therapeutic candidate for the treatment of obesity. Since FGF21 production is regulated by various nutritional factors, we analyze the impact of low protein intake on circulating levels of this growth hormone in mice and in a sub cohort of the PREDIMED ( Prevención con Dieta Mediterránea ) trial. We also describe the role of hepatic FGF21 in metabolic adaptation to a low‐protein diet (LPD). Methods and results: We fed control and liver‐specific Fgf21 knockout (L Fgf21 KO) mice a LPD. This diet increased FGF21 production by inducing its overexpression in liver, and this correlated with a body weight decrease without changes in food intake. The LPD also caused FGF21‐dependent browning in subcutaneous white adipose tissue (scWAT), as indicated by an increase in the expression of uncoupling protein 1 (UCP1). In a subgroup of 78 individuals from the PREDIMED trial, we observed an inverse correlation between protein intake and circulating FGF21 levels. Conclusion: Our results reinforce the involvement of FGF21 in coordinating energy homeostasis under a range of nutritional conditions. Moreover, here we describe an approach to increase the endogenous production of FGF21, which if demonstrated functional in humans, could generate a treatment for obesity.